The stratigraphy and history of Mars' northern lowlands through mineralogy of impact craters: A comprehensive survey. Issue 9 (9th September 2017) - Pan, Lu; Ehlmann, Bethany L.; Carter, John; Ernst, Carolyn M.
Abstract: The basin‐filling materials of the northern lowlands, which cover approximately one third of Mars' surface, record the long‐term evolution of Mars' geology and climate. The buried stratigraphy was inferred through analyses of impact crater mineralogy, detected using data acquired by the Compact Reconnaissance Imaging Spectrometer for Mars. Examining 1045 impact craters across the northern lowlands, we find widespread olivine and pyroxene and diverse hydrated/hydroxylated minerals, including Fe/Mg smectite, chlorite, prehnite, and hydrated silica. The distribution of mafic minerals is consistent with infilling volcanic materials across the entire lowlands ( 1–4 × 10 7 km 3 ), indicating a significant volume of volatile release by volcanic outgassing. Hydrated/hydroxylated minerals are detected more frequently in large craters, consistent with the scenario that the hydrated minerals are being excavated from deep basement rocks, beneath 1–2 km thick mafic lava flows or volcaniclastic materials. The prevalences of different types of hydrated minerals are similar to statistics from the southern highlands. No evidence of concentrated salt deposits has been found, which would indicate a long‐lived global ocean. We also find significant geographical variations of local mineralogy and stratigraphy in different basins (geological provinces), independent of dust cover. For example, many hydrated and mafic minerals are newly discovered within the polar Scandia region (>60°N), and Chryse Planitia has more mafic mineral detections than other basins, possibly due to a previously unrecognized volcanic source. Key Points: The presence of diverse hydrated minerals in lowland craters is consistent with excavation of an aqueously altered ancient basement Widespread mafic minerals associated with impact craters indicate buried volcanic units with calculated volumes greater than prior estimates No strong evidence for widespread carbonate or evaporative salts has been found to support the hypothesis of a global ocean Plain Language Summary: The northern lowlands of Mars (encompassing one third of the planet's surface area) could have hosted a global ocean in the past. The lowlands are composed of several topographic depressions ("basins") filled with sediments, which mask the nature of the underlying crust. Impact craters excavate up to several kilometers into the subsurface of the lowlands and expose the hidden record of its geologic history. Our comprehensive survey of the subsurface mineralogy excavated by these impact craters reveals widespread volcanic and hydrated silicate minerals. We did not find widespread carbonate, chloride, or sulfate salts, which would have suggested a long‐lived global ocean. However, our observations do suggest that impact craters have excavated a crust made of 1 to 2 km of volcanic material, which is on top of a water‐altered basement containing hydrated silicate minerals. We have also discovered local variations in the different basins with evidence for new volcanic sources and for hydrated minerals in ancient crust near the north polar cap.